Virtual reality simulation enabling high level immersion in undergraduate nursing education: A systematic review - Pernica Katrin; Virtanen Heli; Lunddahl Bager Ida; Jordan Fiounnuala; Dütthorn Nadin; Stolt Minna (Canada, 2025)
Background and objectives: Virtual reality simulation (VRS) can be used to complement experiential learning, as it enables nursing students to further learn and refine nursing skills outside of the clinical setting. However, gathering evidence for its effectiveness as a teaching method in achieving learning outcomes is still ongoing, and thus there is a lack of systematic synthesis. The objective of this systematic literature review is to analyze VRS scenarios with a high level of immersion and their impact on learning outcomes in nursing education. Methods: A literature search was performed in the MEDLINE, CINAHL, and ERIC databases in November 2022. As a result, fifteen studies were included and analyzed using deductive content analysis. Results: The studies reported twelve different scenarios for virtual reality simulations with high levels of immersion, the focus of which was on acute critical care, broader nursing processes, neonatal and pediatric care, single nursing interventions, and observation of patients’ symptoms. The associated learning objectives were mainly achieved in the domains of cognition and psychomotor skills. Conclusions: There are several VRS scenarios that show potential for use in nursing education. The VRS scenarios are effective in improving learning outcomes, particularly those related to knowledge and skills. Overall, the supportive body of evidence gained through this review may help nurse educators in integrating virtual simulations in their curricula. In the future, nursing and adult learning theories should be given greater consideration, and the aspect of affective learning could be included in design and implementation. Moreover, future research could benefit from exploring the long-term effects of learning after using VRS with a high level of immersion to provide valuable evidence for developing VRS teaching methods in nursing.